Imatinib-induced interstitial pneumonitis – a literature review and case report - Olga Hilda Orasan; Andreea Maria Stefan; Iulia Minciuna; Adela Sitar-Taut; George Ciulei; Simina Tarmure; Ioana Para; Flaviu Muresan; Ovidiu Fabian; Sorina Cezara Coste; Vasile Negrean; Angela Cozma; et al. (Journal of Mind and Medical Sciences)
Imatinib is generally well tolerated, with mild common side effects such as nausea and vomiting, diarrhea, muscle cramps, fatigue, skin rash and edema; however, pulmonary complications are uncommon. A 73-year-old woman undergoing one month treatment with Imatinib for chronic myeloid neoplasm associated with eosinophilia was admitted for sudden alteration of her performance status, dyspnea at rest and productive cough. On clinical examination, the patient was hypoxic (oxygen saturation on room air was 87%), and auscultation of her lungs revealed diffuse bilateral fine crackles. Computed tomography showed bilateral pulmonary interstitial syndrome. Imatinib was discontinued and the patient received systemic corticosteroid therapy and oxygen therapy. After one month, the symptoms and radiological findings were resolved. When Imatinib therapy was resumed, respiratory symptoms reappeared, which is why treatment with Imatinib was interrupted. Imatinib-induced pneumonitis should take into consideration when patients develop respiratory symptoms or abnormal pulmonary radiological features.